Minimal Residual Disease in Multiple Myeloma: State of the Art and Applications in Clinical Practice - Gozzetti, Alessandro (J Pers Med, 2020)
Novel drugs have revolutionized multiple myeloma therapy in the last 20 years, with median survival that has doubled to up to 8–10 years. The introduction of therapeutic strategies, such as consolidation and maintenance after autologous stem cell transplants, has also ameliorated clinical results. The goal of modern therapies is becoming not only complete remission, but also the deepest possible remission. In this context, the evaluation of minimal residual disease by techniques such as next-generation sequencing (NGS) and next-generation flow (NGF) is becoming part of all new clinical trials that test drug efficacy. This review focuses on minimal residual disease approaches in clinical trials, with particular attention to real-world practices.